Proceedings of the 2015 International Conference on Recent Advances in Computer Systems 2016
DOI: 10.2991/racs-15.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Secure Calls and Caller ID Spoofing Countermeasures Towards building a Cyber Smart Societies

Abstract: Caller Identification (CallerID) is a service provided by the service providers that enables the receiver of the call to know who is trying to call him. Now a days, the caller ID service is used by many public and private organizations to contact their customers in order to exchange private information for authentication purposes. The unified caller ID for all the outgoing series of call connections, establishes an initial chain of trust between the caller and the callee. However, an increasing trends is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A considerable volume of research is reported on the authentication [5,[35][36][37][38][39][40][41]48] and on key agreement [18,[42][43][44][45][46] process to overcome the security gap that needs improvement in the recently proposed symmetric [13], and asymmetric security solutions [17]. Machine learning based authentication [2,4,46] and aggregation [47] is proposed to overcome the security flaws in the dynamic environments.…”
Section: Related Workmentioning
confidence: 99%
“…A considerable volume of research is reported on the authentication [5,[35][36][37][38][39][40][41]48] and on key agreement [18,[42][43][44][45][46] process to overcome the security gap that needs improvement in the recently proposed symmetric [13], and asymmetric security solutions [17]. Machine learning based authentication [2,4,46] and aggregation [47] is proposed to overcome the security flaws in the dynamic environments.…”
Section: Related Workmentioning
confidence: 99%